Inequality aversion causes equal or unequal division in alternating-offer bargaining - Kohler, Stefan; Schlag, Karl H. (Bulletin of economic research, 2019)
A solution to Rubinstein (1982)'s open-ended, alternating-offer bargaining problem for two equally patient bargainers who exhibit similar degrees of inequality aversion is presented. Inequality-averse bargainers may experience envy if they are worse off, and guilt if they are better off, but they still reach agreement in the first period under complete information. If the guilt felt is strong, then the inequality-averse bargainers split a pie of size one equally regardless of their degree of envy. If the guilt experienced is weak, then the agreed split is tilted away from the Rubinstein division towards a more unequal split whenever the degree of envy is smaller than the discounted degree of guilt. Envy and weak guilt have opposite effects on the equilibrium division of the pie, and envy has a greater marginal impact than weak guilt. Equally inequality-averse bargainers agree on the Rubinstein division if the degree of envy equals the discounted degree of guilt. As both bargainers' sensation of inequality aversion diminishes, the bargaining outcome converges to the Rubinstein division.